Microalgae biomass deconstruction using green solvents: Challenges and future opportunities. (February 2023) - Raj, Tirath; Morya, Raj; Chandrasekhar, K; Kumar, Deepak; Soam, Shveta; Kumar, Ravindra; Patel, Anil Kumar; Kim, Sang-Hyoun
Graphical abstract: Highlights: Microalgal represents 3G feedstock for renewable fuels, chemical and energy production. Green pretreatment/ extraction processes for sugars, lipids and proteins have been outlined. Aqueous biphasic systems with suitable cations/ anions may promote high extraction yield. Integrated microalgal biorefinery development will enhance bioresource recovery. Biodegradability and recyclability are core areas that need to explore for scale-up activity. Abstract: Microalgae enable fixation of CO2  into carbohydrates, lipids, and proteins through inter and intracellularly biochemical pathways. These cellular components can be extracted and transformed into renewable energy, chemicals, and materials through biochemical and thermochemical transformation processes. However, recalcitrant cell wall and lack of environmentally benign efficient pretreatment processes are key obstacles in the commercialization of microalgal biorefineries. Thus,  current article describes the microalgal chemical structure, type, and structural rigidity and summarizes the traditional pretreatment methods to extract cell wall constituents. Green solvents such as ionic liquid (ILs), deep eutectic solvents (DES), and natural deep eutectic solvents (NDESs) have shown interesting solvent characteristics to pretreat biomass with selective biocomponent extraction from microalgae. Further research is needed in task-specific IL/DES design, cation–anion organization, structural activity understanding of ILs-biocomponents, environmental toxicity, biodegradability, and recyclability for deployment of carbon–neutral technologies. Additionally, coupling the microalgal industry with biorefineries may facilitate waste management, sustainability, and gross revenue.